Analysis of Social Adaptation Problems in Adult Schools - Alifanovienė, Daiva; Vaitkevičienė, Asta (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryIn this paper, we analyze the social and educational problems of adult school students. The students have to overcome the learning failures from the past, to manage the schedules of studies and work, to adapt to the requirements of teachers, to create and sustain the relationships in the class. The aim of this empirical research was to reveal the factors of the adaptation process.Key words: adult school, students, social adaptation.